Ion Acoustic Peregrine Soliton Under Enhanced Dissipation - Pathak, Pallabi (Frontiers in Physics, 2021)
The effect of the enhanced Landau damping on the evolution of ion acoustic Peregrine soliton in multicomponent plasma with negative ions has been investigated. The experiment is performed in a multidipole double plasma device. To enhance the ion Landau damping, temperature of the ions is increased by applying a continuous sinusoidal signal of frequency close to the ion plasma frequency 1 MHz to the separation grid. The spatial damping rate of ion acoustic wave is measured by the interferometry. The damping rate of ion acoustic wave increases with the increase in voltage of the applied signal. At higher damping rate, the Peregrine soliton ceases to show its characteristics leaving behind a continuous envelope.